Education Attainment in Public Administration Around the World : Evidence from a New Dataset - Arezki, Rabah (IMF Working Papers; Working Paper, 2012)
The paper provides a detailed description of a novel dataset on education attainment in public administrations covering the period 1981-2011 for 178 countries. The dataset uses information extracted from CVs for over 130,000 mid to senior level officials from mainly central banks and ministries of economy and finance. Our main finding is that there is little heterogeneity across regions when considering a non quality-adjusted measure of education attainment in public administrations. Adjusting our measure for quality, using a country wide academic ranking, reveals important cross-regional heterogeneity differing from that of standard measures of education attainment for the general population. The dataset also allows us to uncover important patterns in public administrations' education attainment along gender and seniority across regions. We further use the dataset to explore a few applications which provide some evidence of (i) the importance of salary incentives in attracting highly educated staff and (ii) a positive association between education attainment in public administrations and government effectiveness (e.g. higher tax revenue mobilization, limiting corruption, better public finance management and private market support).